2012
DOI: 10.4236/ijoc.2012.23034
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Benign Electrophilic Halogenation of Naphthalenes by H<sub>2</sub>O<sub>2</sub>—Alkali Metal Halides in An Aqueous Cationic Micellar Media

Abstract: An efficient and greener protocol for the synthesis of 1-halo-naphthols by the action of hydrogen peroxide and alkali metal halides in aqueous micellar media is been described in the present work. This is an environmentally clean and safe procedure, which involved insitu generation of the active halogen in presence of alkali halides. Cationic surfactants such as cetyltrimethylammoniumbromide (CTAB) and cetyltrimethylammoniumchloride (CTAC) were found to facilitate efficiency of halogenation in aqueous media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…1-Hexyloxy-4-iodobenzene, 1-hexyloxy-2-iodobenzene, N , N -diethyl-4-iodoaniline, N , N -dibutyl-4-iodoaniline, 1,6-bis­(4-iodophenoxy)­hexane, 1-iodo-2-7-dimethoxynaphthalene, iodophenantharene, idooanthracene, 1-(4-iodophenyl)-1 H -pyrrole, 1-(4-iodophenyl)-pyrrolidine, 1-(2-iodophenyl)-pyrrolidine, 2-(4-chlorophenyl)-3-iodo-7-methylimidazo­[1,2- a ]­pyridine, 2-(4-chlorophenyl)-3-iodoimidazo­[1,2- a ]­pyridine, 6-chloro-2-(4-chlorophenyl)-3-iodoimidazo­[1,2- a ]­pyridine, 2-(4-bromophenyl)-6-chloro-3-iodoimidazo­[1,2- a ]­pyridine, 1-iodo-2-isobutoxynaphthalene, 9-hydroxy-1 H -phenalenone, 9-(methylamino)-1 H -phenalenone, ( E )-ethyl­(9-(methylamino)-1 H -phenalen-1-ylidene)­oxonium tetrafluoroborate salt, and 9,9′-(ethane-1,2-diylbis­(azanediyl))­bis­(1 H -phenalenone) were synthesized according to the reported literature.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-Hexyloxy-4-iodobenzene, 1-hexyloxy-2-iodobenzene, N , N -diethyl-4-iodoaniline, N , N -dibutyl-4-iodoaniline, 1,6-bis­(4-iodophenoxy)­hexane, 1-iodo-2-7-dimethoxynaphthalene, iodophenantharene, idooanthracene, 1-(4-iodophenyl)-1 H -pyrrole, 1-(4-iodophenyl)-pyrrolidine, 1-(2-iodophenyl)-pyrrolidine, 2-(4-chlorophenyl)-3-iodo-7-methylimidazo­[1,2- a ]­pyridine, 2-(4-chlorophenyl)-3-iodoimidazo­[1,2- a ]­pyridine, 6-chloro-2-(4-chlorophenyl)-3-iodoimidazo­[1,2- a ]­pyridine, 2-(4-bromophenyl)-6-chloro-3-iodoimidazo­[1,2- a ]­pyridine, 1-iodo-2-isobutoxynaphthalene, 9-hydroxy-1 H -phenalenone, 9-(methylamino)-1 H -phenalenone, ( E )-ethyl­(9-(methylamino)-1 H -phenalen-1-ylidene)­oxonium tetrafluoroborate salt, and 9,9′-(ethane-1,2-diylbis­(azanediyl))­bis­(1 H -phenalenone) were synthesized according to the reported literature.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Preparation of the Substrates. 1-Hexyloxy-4-iodobenzene, 82 1hexyloxy-2-iodobenzene, 83 N,N-diethyl-4-iodoaniline, 84 N,N-dibutyl-4-iodoaniline, 85 1,6-bis(4-iodophenoxy)hexane, 86 1-iodo-2-7-dimethoxynaphthalene, 87 iodophenantharene, 88 idooanthracene, 89 1-(4iodophenyl)-1H-pyrrole, 24 1-(4-iodophenyl)-pyrrolidine, 90 1-(2-iodophenyl)-pyrrolidine, 91 93 1-iodo-2-isobutoxynaphthalene, 94 9-hydroxy-1H-phenalenone, 65 9-(methylamino)-1H-phenalenone, 65 (E)-ethyl(9-(methylamino)-1H-phenalen-1-ylidene)oxonium tetrafluoroborate salt, 95 and 9,9′-(ethane-1,2-diylbis(azanediyl))bis(1H-phenalenone) 66 were synthesized according to the reported literature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…54 Few other methods used KI with K 2 FeO 4 48b and KI with CTAB/H 2 O 2 . 55 All the aqueous phase halogenation methods mainly focused on monohalogenation but not on regioselective dihalogenations. Further, a co-reagent or a base is a necessary condition for halogenations.…”
Section: Introductionmentioning
confidence: 99%
“…Grinding, milling, shearing, scratching and polishing provide the mechanical impact for mechanochemistry. 51 The pioneering work of Toda 52 has shown that many exothermic reactions can be accomplished in high yield by just grinding solids together using mortar and pestle, a technique known as 'Grindstone Chemistry' which is one of the 'Green Chemistry Techniques'. Reactions are initiated by grinding, with the transfer of very small amounts of energy through friction.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state reactions occur more efficiently and more selectively than does the solution reaction. 52 This method is superior to conventional method; since it is eco-friendly, high yielding requires no special apparatus, non-hazardous, operationally simple and convenient 53 . Here we used simple mortar and pastel for grinding purpose and microwave irradiation to complete the reaction.…”
Section: Introductionmentioning
confidence: 99%